The EDI Movement: The Classroom, the Curriculum, the Students - Peters, Brian (Apprendre et enseigner aujourd’hui, 2024)
In education, over the past decade, rather intense EDI movements have been taking place from basic hiring in the job force, to trends on campus, and to revamping sometimes very flat or monotoned curricula. EDI at heart is wonderful. My focus here is to open-up a discussion about EDI but to also look at problems with misusing/misunderstanding EDI. EDI grew out of equal opportunity, and important career focus that enabled companies, staff, and hiring committees to understand demographics and aim for diverse representations. Educational institutions of all kinds offer frequent EDI workshops that not only sensitize participants to EDI current realities, but the contemporary vocabulary and related lexicons for marginalized groups and peoples, and a way to become aware that not everyone is the same, that everyone has their own story. Furthermore, EDI is crucial in neutralizing sexism, racism, homophobia and transphobia in the workplace and needs to be applied with compassion and kindness to be truly effective and not alienate potential EDI allies.